It's easy, first define
Now, differentiate implicity, and yields
And we're done.
I have a formula that I am trying to differentiate, but having lots of problems with it:
r(s)= tan^-1 s, root of 2 /2 log(1+s^2), s - tan^-1 s)
r'(s) = ( ( 1+s^2)^-1, root of 2 s(1+s^2)^-1, 1- (1+s^2)-1
= (1+s^2)^-1 (1, root of 2 s, s^2)
I dont know how the derivative of tan^-1(s) = 1/1+s^2, can anyone explain?
And cannot follow how all the derivatives work out, can anyone talk me through it? I have exam shortly and ally need to get to know these off by heart.